Towards a green trade and investment strategy for Africa - Mbeva, K (Blavatnik School of Government, University of Oxford, 2023)
Climate change is reshaping the world economy in significant ways, from affecting critical sectors in vulnerable economies, to heightening the race by major economies to dominate green and climate technologies. To address these challenges and also secure the emerging opportunities, many countries are increasingly adjusting trade rules around climate goals. While discussion has mainly focused on the global North, as well as major emerging economies such as China, these changes have significant implications for other countries, especially those in the global South. For African countries which have adopted and begun implementing ambitious regional economic integration initiatives, climate-proofing its development is an imperative.